Theology chronicle: Images of God in the Old Testament: Yahweh – loving father and mother - Groenewald, Alphonso (Verbum et ecclesia, 2006)
This theology chronicle proceeds from the Marcionite idea of the cruel God of the Old Testament. This idea today is still well and alive with church members, and even with students of Biblical Studies and Theology. The author then takes the reader on a short journey through some of the most sublime love texts in the Old Testament, portraying Yahweh (the God of Israel) as a loving father and even as a loving mother/wife. The article concludes with an appeal towards the reader to once again discover the beauty of the Old Testament as well as Old Testament texts.